Effectiveness of teriparatide in in improving healing rates and bone-turnover markers of osteoporotic hip fracture: a meta-analysis - Lin Luo; Lin, Jiaru; Ma, Wenzhe; Fan, Junming (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the effect of subcutaneous teriparatide therapy on fracture healing rate and change in bone mass density in osteoporotic hip fractures. Method: The meta-analysis was done from September to December 2022, and comprise literature search on Wanfang, CNKI, VIP, PubMed, Embase, Cochrane Library, and Web of Science databases from the establishment of the respective database till December 2022. The relevant journals of the library of Macao University of Science and Technology, China, were manually searched for randomised controlled trials of teriparatide in the treatment of osteoporotic hip fractures. The shortlisted studies were subjectd to Cochrane Risk of Bias tool and the Jadad Rating Scale. Meta-analysis was done using the RevMan 5.4 software provided by the Cochrane Collaboration Network. Fracture healing rate and bone mineral density were the primary outcome measures, while mortality, adverse events, malformations, complications, subsequent fractures, timed-up-and-go test, visual analogue scale score, and procollagen type I N-terminal propeptide were the secondary outcome measures. Results: Of the 1,094 articles retrieved, 8(0.7%) randomised controlled trials were analysed. There were 744 patients; 372(50%) in the teriparatide group and 372(50%) in the control group. Fracture healing rate was not significantly different (p=0.82), while bone mineral density was significantly different between the groups (p<0.001). Mortality, adverse events, deformity, and complications were not significantly different (p>0.05), while subsequent fractures, timed-up-and-go score, visual analogue scale score and procollagen type I N-terminal propeptide were significantly different between the groups (p<0.05). ---Continue